Clinical and radiographic medium‐term evaluation on patients with developmental dysplasia of the hip, who were submitted to open reduction, capsuloplasty and Salter osteotomy()() - da Rocha, Válney Luiz (Rev Bras Ortop, 2014)
OBJECTIVE: to evaluate the clinical and radiographic medium‐term results from surgical treatment of developmental dysplasia through open reduction, Salter et al.’s osteotomy and capsuloplasty. METHODS: 13 patients were evaluated, 13 hips treated surgically by the proposed technique between 2004 and 2011. A clinical and radiographic evaluation was conducted by Dutoit et al. and Severin et al. criteria, respectively. RESULTS: the acetabular preoperative index for the 13 surgically treated hips ranged from 27° to 50° (average of 36), and after surgical correction to 18.5° (10–28°), so that the evaluations of preoperative and postoperative acetabular indexes showed up significant statistic reduction (p < 0.05). Regarding the postoperative clinical evaluation, it was found: nine excellent hips (69.2%), three good ones (23.1%), no fair hips (0%) and a poor one (7.7%). In radiographic evaluation, it was found: six excellent hips (46.1%), three good ones (23.1%), no fair hips (0%) and four poor ones (30.8%). Therefore, favorable results were obtained (92.3%), with grouped hips with excellent and good ratings as satisfactory and with fair and bad ratings as unsatisfactory. It is also important to notice that there was no significance among occurrence of complications, the patient's age, the time of surgery and the preoperative acetabular index (p > 0.05). As complications occurred, it was found that three subluxations and a subluxation associated with avascular necrosis of the femoral head. CONCLUSION: open reduction, Salter et al.’s osteotomy and capsuloplasty are seen to be a viable option for the treatment of developmental dysplasia of the hip, according to clinical and radiological medium‐term evaluations.